Skeletal muscle proteome differs between young APOE3 and APOE4 targeted replacement mice in a sex-dependent manner - Johnson, Chelsea N.; Lysaker, Colton R.; McCoin, Colin S.; Evans, Mara R.; Thyfault, John P.; Wilkins, Heather M.; Morris, Jill K.; Geiger, Paige C. (Frontiers in Aging Neuroscience, 2024)
IntroductionApolipoprotein E4 (APOE4) is the strongest genetic risk factor for Alzheimer's disease (AD), yet it's unclear how this allele mediates risk. APOE4 carriers experience reduced mobility and faster decline in muscle strength, suggesting skeletal muscle involvement. Mitochondria are critical for muscle function and although we have reported defects in muscle mitochondrial respiration during early cognitive decline, APOE4-mediated effects on muscle mitochondria are unknown.MethodsHere, we sought to determine the impact of APOE4 on skeletal muscle bioenergetics using young, male and female APOE3 (control) and APOE4 targeted replacement mice (n = 8 per genotype/sex combination). We examined the proteome, mitochondrial respiration, fiber size, and fiber-type distribution in skeletal muscle.ResultsWe found that APOE4 alters mitochondrial pathway expression in young mouse muscle in a sex-dependent manner without affecting respiration and fiber size or composition relative to APOE3. In both sexes, the expression of mitochondrial pathways involved in electron transport, ATP synthesis, and heat production by uncoupling proteins and mitochondrial dysfunction significantly differed between APOE4 and APOE3 muscle. For pathways with predicted direction of activation, electron transport and oxidative phosphorylation were upregulated while mitochondrial dysfunction and sirtuin signaling were downregulated in female APOE4 vs. APOE3 muscle. In males, sulfur amino acid metabolism was upregulated in APOE4 vs. APOE3 muscle.DiscussionThis work highlights early involvement of skeletal muscle in a mouse model of APOE4-linked AD, which may contribute to AD pathogenesis or serve as a biomarker for brain health.